Seulangkȇ as a Model for Enhancing Principal Competence in South Aceh: a Study on the Cultural Approach Effectiveness - Maidar, Maidar; Gultom, Syawal; Darwin, Darwin (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2025)
The impact of culture on learning has been extensively acknowledged by authorities such as Vygotsky. This study aimed to evaluate the efficacy of the Acehnese culture-based training model, Seulangke, and to enhance the competencies of state secondary school administrators in South Aceh Regency, Indonesia. This research employs a qualitative methodology with a cultural perspective. This paper employs a pre-experimental design characterized by a one-shot case study involving 27 principals in South Aceh. Data collection was conducted by testing and paperwork, thereafter analyzed with the t-test method utilizing SPSS version 23. Differences in learning results exist between training participants utilizing the Jigsaw training model (experiment A) and the Seulangkê model (experiment B) among school principals. The study stated that the experimental data indicated a disparity in learning outcomes between experiment A, which yielded a score of 69.63, and experiment B, which achieved a score of 75.00. This indicates that the application of Experiment B (Seulangkê Model) in education is superior to the control Experiment B (Jigsaw Model). The statistical examination of the "t-test" indicates a t-count of -2.887, with a significance level of 5% (95% confidence interval) and 52 degrees of freedom. If the t-count is situated in that region, H0 is dismissed. Consequently, it can be inferred that the learning outcomes of participants in experimental classes A and B regarding principal competence (personality, managerial skills, entrepreneurship, supervision, and social abilities) are not identical or significantly different, indicating that there are disparities in the learning outcomes of the training participants, with experiment B outperforming experiment A.